Evaluation of Porang Flour (Amorphophallus muelleri) as Natural Filler for Enhancing Urea Formaldehyde and Citric Acid Adhesives in Plywood Production - Imam Busyra Abdillah; Alifah Syahfitri; Muhammad Ilham Aulia; Abdus Syukur; Sarah Augustina; Sukma Surya Kusumah; Muhammad Adly Rahandi Lubis; Jajang Sutiawan; Mahdi Mubarok; Rita Kartika Sari; Naresworo Nugroho; Yusuf Sudo Hadi; et al. (BioResources, 2025)
This study explores the potential of porang flour (Amorphophallus muelleri) as a sustainable filler in urea formaldehyde (UF) and citric acid (CA) adhesives, highlighting its effect on enhancing plywood performance. The physical and mechanical properties of plywood bonded with varying compositions of porang flour (0%, 10%, 20%) were evaluated according to Japanese Agricultural Standard (JAS 233:2003) for plywood. Three-layer plywood panels were manufactured using sengon wood and both types of adhesives. The results showed that adding porang flour to UF and CA adhesives significantly increased the solids content and improved physical and mechanical properties. Plywood bonded with UF exhibited superior density, water absorption, thickness swelling, and shear strength properties. Conversely, plywood bonded with CA adhesive showed better results in moisture content, modulus of elasticity (MOE), and modulus of rupture (MOR). Overall, adding 10% porang flour was optimal for improving plywood’s physical and mechanical properties. These findings suggest that porang flour is an eco-friendly additive that can enhance the performance of natural adhesives in plywood manufacturing, providing a greener alternative to conventional adhesives.